The impact of Azolla (Azolla pinnata R.Br.) dietary supplementation on broiler chicken production performance and serum biochemical profile - Belagoune, Asma; Beghoul, Saber; Djemai, Samir; Hafid, Kahina; Amireche, Douaa; Mansour, Amir (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2024)
For decades, Algeria has faced difficulties related to importing raw materials for livestock feed, such as soybeans and corn. The aim of this study was to valorize Azolla as an important source of nutrients, particularly proteins, in broiler production. For this purpose, 60 broiler chicks of the Cobb 500 breed were divided into two groups, each containing three repetitions of 10 birds. The diets of the tested and control groups were the same, except for the tested group, which received Azolla as a supplement. The nutritional value of Azolla incorporated into the diet was assessed chemically. Liveweight, feed intake, feed conversion ratio, offal weight, carcass yield, and biochemical profile for both groups were observed and compared. The intake of Azolla had no impact on production yield (p˃0.05); however, the best liveweight at sacrifice was obtained in the Azolla group, with a value of 2600.67 g, whereas the mean recorded in the control group was 2431.67 g. Regarding the weight and yield of offal and carcass, we found the same observation: the highest weight of thighs and wings was recorded in the Azolla group. All blood biochemical parameters examined (glucose, creatinine, cholesterol, triglyceride, high-density lipoprotein (HDL), total protein, albumin, and alanine aminotransferase (ALT)) showed no significant difference, except for aspartate aminotransferase (AST), which was found to be significantly higher in the Azolla group (P˂0.05). Azolla pinnata, a source of unconventional protein, may therefore be an alternative to the costly poultry feed used in Algeria.